High-performance conductive carbon black as well as preparation method and application thereof
By treating the surface of conductive carbon black with oxidants and organic acids to generate acyl groups and then polymerizing a conductive polymer layer in situ, the problems of uneven particle size distribution and poor conductivity of traditional carbon black are solved, and a high-performance conductive carbon black suitable for high-voltage cables is prepared.
Patent Information
- Application Number
- CN202511048254.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-29
- Publication Date
- 2025-11-18
AI Technical Summary
Traditional carbon black granulation methods have difficulty controlling particle size distribution and conductivity, resulting in poor conductivity and limiting its application in high-voltage cables.
The surface of conductive carbon black is treated with oxidants and organic acids to generate acyl groups and polymerize a conductive polymer layer on the surface in situ, thereby improving the uniformity of particle size distribution and conductivity.
High-performance conductive carbon black with uniform particle size distribution and excellent conductivity was prepared, which is suitable for high-voltage cable shielding layers. The resistivity is as low as 3.36 Ω·cm and the particle size distribution index is as low as 0.51.
Smart Images

Figure CN120966283A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of carbon black preparation technology, specifically to a high-performance conductive carbon black, its preparation method, and its application. Background Technology
[0002] The structure of a high-voltage cable, from the inside out, includes a conductor layer, a semi-conductive shielding layer, an insulation layer, a metallic shielding layer, and a sheath layer. The main function of the shielding layer is to reduce the interfacial gap between the conductor core and the insulation layer, homogenize the electric field of the insulation layer, and suppress space charge injection. As a crucial component of high-voltage cables, the performance of the semi-conductive shielding layer material directly affects the cable's safe operation and service life. Conductive carbon black is one of the most important components of the shielding layer. To meet the requirements of ultra-smoothness and electrical properties of the semi-conductive shielding material, the selected conductive carbon black typically needs to possess uniform particle size distribution and high conductivity.
[0003] The granulation stage of carbon black is crucial to the performance of the final carbon black product, determining key indicators such as particle size, specific surface area, structure, and surface chemical properties. However, traditional granulation methods struggle to control the particle size distribution and conductivity of conductive carbon black, often resulting in a wide particle size distribution and poor conductivity, thus limiting its application in high-voltage cables. Therefore, there is an urgent need to improve existing carbon black granulation processes to meet the higher requirements of the high-voltage cable industry for carbon black materials in semi-conductive shielding layers. Summary of the Invention
[0004] To address the shortcomings of existing technologies, this invention provides a method for preparing high-performance conductive carbon black. First, the surface of conductive carbon black is treated sequentially with an oxidant and an organic acid to obtain acyl-oxidized conductive carbon black containing acyl groups on its surface. Then, a conductive polymer layer is generated by in-situ polymerization on its surface. The introduction of acyl groups improves the uniformity of particle size distribution of the conductive carbon black, and the introduction of the conductive polymer layer can improve the conductivity of the conductive carbon black.
[0005] Another object of the present invention is to provide a high-performance conductive carbon black.
[0006] Another object of the present invention is to provide an application of high-performance conductive carbon black.
[0007] The above-mentioned objective of this invention is achieved through the following technical solution:
[0008] A method for preparing high-performance conductive carbon black includes the following steps:
[0009] S1. Conductive carbon black raw material is treated sequentially with an oxidant and an organic acid to obtain acyl-oxidized conductive carbon black;
[0010] S2. The acyl oxidized conductive carbon black obtained in step S1 is mixed with conductive polymer monomers, initiators and binders, and subjected to polymerization reaction and granulation to obtain high-performance conductive carbon black.
[0011] In the preparation method provided by this invention, the conductive carbon black mainly undergoes surface oxidation and acyl oxidation. The method for preparing high-performance conductive carbon black provided by this invention first modifies the conductive carbon black raw material with acyl oxidation to prevent a wide particle size distribution due to electrostatic adsorption. Subsequently, a conductive polymer layer is generated in situ on the surface of the acyl-oxidized conductive carbon black, significantly improving its conductivity. Specifically, in step S1, treating the conductive carbon black raw material with an oxidant yields carbon black with oxygen-containing functional groups on its surface. Adding an organic acid further induces esterification of these oxygen-containing functional groups on the carbon black surface, resulting in conductive carbon black with acyl groups on its surface. After introducing acyl groups onto the surface of conductive carbon black in step S1, the large steric hindrance and electron-donating effect of the acyl groups effectively prevent carbon black particles from approaching each other through steric hindrance and electrostatic repulsion. This reduces electrostatic adsorption and aggregation between conductive carbon black particles, improving the uniformity of particle size distribution (electrostatic adsorption easily leads to particle aggregation, but the strength of adsorption varies, resulting in different degrees of aggregation, which increases the polydispersity and decreases the uniformity of carbon black particle size distribution). In step S2, conductive polymer monomers are polymerized in situ on the surface of the acyl-oxidized carbon black particles to form a conductive polymer layer, which can further improve the conductivity of the conductive carbon black.
[0012] It should be noted that after oxidation modification, various oxygen-containing functional groups such as carboxyl and hydroxyl groups are actually generated on the surface of carbon black. Through extensive experimental research, the inventors of this application discovered that only by using organic acids to oxidize the hydroxyl groups on the carbon black surface can a conductive polymer layer be successfully loaded onto its surface while simultaneously improving the uniformity of carbon black particle size distribution. While using alcohols to esterify the carboxyl groups on the carbon black surface also introduces ester groups, the ester bond orientation is unsuitable, thus failing to achieve the objective of this invention. Specifically, treating the acyloxy group -OCOR formed on the oxidized carbon black surface with organic acids has a conjugated electron-donating effect, which can increase the electron cloud density on the carbon black surface, thereby effectively reducing the aggregation between carbon black particles through electrostatic repulsion. Simultaneously, some of the -OCOR acyloxy groups can be hydrolyzed back to the hydroxyl form in step S2. The hydroxyl group can serve as an initiation site or anchoring point for in-situ polymerization reactions, bonding with the conductive polymer monomers to improve the bonding force between the conductive carbon black and its surface conductive polymer layer, ensuring that the high-performance conductive carbon black does not experience a decrease in conductivity due to the detachment of the conductive layer. If alcohol is used to modify the carbon black surface through esterification in step S1, the resulting ester bond is -COOR. Although both are ester groups, the overall electronic effect of -COOR is electron-withdrawing. Its introduction will reduce the electron cloud density on the carbon black surface, which will result in a large tendency for electrostatic adsorption and aggregation between carbon black particles, and will not improve the particle size uniformity of carbon black.
[0013] It should be noted that, since carbon black particles easily adsorb to each other and form aggregates, the "particle size" mentioned in this invention includes the particle size of carbon black particles in various forms, including single particles and aggregates; that is, all forms of carbon black particles are included in the particle size statistics. In a specific embodiment of this invention, the average particle size of the carbon black is obtained by observing the particle size of 10-15 carbon black particles (which can be aggregates or single particles) in a TEM image and calculating their average value.
[0014] In a specific embodiment of the present invention, the temperature for treating conductive carbon black with an oxidant in step S1 is room temperature, and the time is 24-48 hours.
[0015] Preferably, the mass ratio of the oxidant to the conductive carbon black raw material in step S1 is (8-10):100.
[0016] In a specific embodiment of the present invention, step S1 involves treating the conductive carbon black raw material with an oxidant to obtain oxidized conductive carbon black, wherein the mass percentage of oxygen-containing functional groups in the obtained oxidized conductive carbon black is 2.5-5%.
[0017] Preferably, the oxidant in step S1 includes at least one of potassium permanganate, hydrogen peroxide, and ammonium persulfate.
[0018] Preferably, the mass-to-volume ratio of the conductive carbon black raw material to the organic acid in step S1 is 1 g: (1-10) mL.
[0019] Preferably, the organic acid in step S1 includes at least one of oleic acid, palmitic acid, and acrylic acid.
[0020] In a specific embodiment of the present invention, the temperature for treating conductive carbon black with organic acid in step S1 is room temperature, and the time is 24-48 hours.
[0021] Preferably, the mass percentage of acyl groups in the acyl-oxidized conductive carbon black obtained in step S1 is 1.8-3.5%.
[0022] Preferably, step S1, after treating the conductive carbon black raw material with an oxidant and organic acid, further includes washing and drying steps. More preferably, the washing solution is an ethanol / water mixture. More preferably, the volume ratio of water to ethanol in the ethanol / water mixture is (5-8):(2-5). More preferably, the drying temperature is 120-180°C.
[0023] Preferably, in step S1, the conductive carbon black raw material is treated with an oxidant and an organic acid in a solution environment. The solution includes an organic solvent, which includes at least one of dichloromethane, dimethyl sulfoxide, and n-hexane. More preferably, the mass-to-volume ratio of the conductive carbon black raw material to the organic solvent is 1 g:(50-120) mL.
[0024] Preferably, in step S1, the conductive carbon black raw material is treated with an oxidant and an organic acid in the presence of a catalyst, wherein the catalyst comprises tetrabutylammonium bromide. More preferably, the mass ratio of the catalyst to the conductive carbon black raw material is (1-3):100.
[0025] Preferably, in step S1, the conductive carbon black raw material is treated with an oxidant and an organic acid under stirring conditions, and the stirring speed can be 60-150 rpm.
[0026] In a specific embodiment of the present invention, step S1 is as follows: the conductive carbon black raw material, oxidant and catalyst are added to an organic solvent and stirred. After stirring, oxidized conductive carbon black is obtained. Then, an organic acid is added and the oxidized conductive carbon black is treated under stirring conditions to obtain acyl oxidized conductive carbon black.
[0027] Preferably, the conductive carbon black raw material in step S1 has an average particle size of 20-60 nm, an iodine absorption value of 50-100 g / kg, and an ash content of ≤0.1%.
[0028] More preferably, the conductive carbon black raw material in step S1 has an average particle size of 40 nm, an iodine absorption value of 75 g / kg, a residue of 5 ppm on a 325 mesh sieve, and an ash content of 0.06%.
[0029] In a specific embodiment of the present invention, the conductive carbon black raw material includes conductive carbon black prepared from oil using an oil furnace method. More specifically, the oil includes at least one of anthracene oil, ethylene tar, and coal tar.
[0030] Preferably, the mass fractions of each raw material in step S2 are: 100 parts of acyl oxidized conductive carbon black, 10-30 parts of conductive polymer monomer, 6-30 parts of initiator, and 1.0-2.5 parts of binder.
[0031] In a specific embodiment of the present invention, the polymerization reaction described in step S2 is carried out during the mixing process.
[0032] Preferably, the conductive polymer monomer in step S2 includes at least one of pyrrole, aniline, and thiophene.
[0033] Preferably, the initiator in step S2 includes at least one of ferric chloride, potassium dichromate, potassium iodate, manganese dioxide, and benzoyl peroxide.
[0034] Preferably, the binder in step S2 comprises lignin sulfonate.
[0035] More preferably, the binder in step S2 is introduced in solution form, wherein the solvent of the solution includes water. In a specific embodiment of the invention, granulation water (i.e., an aqueous solution in which the solute is the binder) is used to introduce the binder.
[0036] Preferably, the mixing and granulation in step S2 are carried out in a toothed granulator.
[0037] Preferably, the mixing in step S2 is as follows: first, acyl oxidized conductive carbon black is added to the stirring tooth granulator, the remaining components are mixed separately and then injected into the stirring tooth granulator through atomization, and then mixed.
[0038] Preferably, the mixing in step S2 is carried out under stirring conditions, and the stirring speed is 60-150 rpm.
[0039] Preferably, step S2 further includes a sieving step after granulation, wherein the sieve used for sieving has a mesh size of 1 to 2 mm.
[0040] Preferably, step S2, after granulation and before sieving, further includes washing and drying steps. More preferably, the washing solution is an ethanol / water mixture. More preferably, the volume ratio of water to ethanol in the ethanol / water mixture is (5-8):(2-5). More preferably, the drying temperature is 120-180°C. More preferably, the washing is performed ≥2 times.
[0041] This invention also protects the high-performance conductive carbon black prepared by the above preparation method.
[0042] The present invention also protects a high-voltage cable shielding layer, wherein the raw materials for preparing the high-voltage cable shielding layer include the above-mentioned high-performance conductive carbon black.
[0043] Preferably, the high-voltage cable shielding layer comprises the following raw materials in parts by mass:
[0044] 27-35 parts high-performance conductive carbon black, 60-70 parts matrix resin, 0.1-0.5 parts antioxidant, and 2-4 parts crosslinking agent.
[0045] More preferably, the resin includes at least one of ethylene-vinyl acetate, ethylene-ethyl acrylate, and ethylene-butyl acrylate.
[0046] The present invention also protects a high-voltage cable, the high-voltage cable including the high-voltage cable shielding layer.
[0047] In a specific embodiment of the present invention, the high-voltage cable comprises, from the inside out, a conductor core, a high-voltage cable shielding layer, an insulation layer, and a metal protective layer.
[0048] Compared with the prior art, the present invention has the following beneficial effects:
[0049] Compared with traditional conductive carbon black, the high-performance conductive carbon black prepared by this invention has advantages such as uniform particle size distribution and excellent conductivity. Its resistivity is as low as 3.36 Ω·cm and its particle size distribution index is as low as 0.51, making it widely applicable to subsequent applications. Attached Figure Description
[0050] Figure 1 The infrared spectrum of the oxidized conductive carbon black obtained in step S1 of Example 1 of the present invention. Detailed Implementation
[0051] The present invention will be further described below with reference to specific embodiments, but the embodiments do not limit the present invention in any way. Unless otherwise stated, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents. The raw material information used in each embodiment and comparative example is as follows:
[0052] Conductive carbon black raw material: Conductive carbon black prepared from anthracene oil via an oil furnace method, with an average particle size of 40 nm, an iodine absorption value of 75 g / kg, and an oil absorption value of 148 × 10⁻⁶. -5 m 3 / kg, residue on 325 mesh sieve is 5ppm, ash content is 0.06%.
[0053] Example 1
[0054] A method for preparing high-performance conductive carbon black includes the following steps:
[0055] S1. Conductive carbon black raw material was added to n-hexane at a ratio of 1g:100mL. Potassium permanganate and tetrabutylammonium bromide were added at a mass ratio of 100 parts conductive carbon black, 10 parts oxidant and 1 part catalyst. After stirring and mixing for 24h, oxidized conductive carbon black was obtained. Oleic acid was added to the reaction system at a mass-volume ratio of 1g:5mL for conductive carbon black raw material. After stirring and reacting for 24h, the mixture was washed and dried to obtain acyl oxidized conductive carbon black.
[0056] S2. The acyl oxidized conductive carbon black obtained in step S1 is fed into a stirring toothed granulator. The pyrrole monomer, ferric chloride and binder are mixed separately, fully atomized and injected into the granulator through a nozzle. The amount of each raw material added is as follows: 100 parts of acyl oxidized conductive carbon black, 15 parts of pyrrole monomer, 13.5 parts of ferric chloride and 1.2 parts of sodium lignosulfonate (the sodium lignosulfonate is dissolved in 10 parts of water to obtain granulation water and then added in the form of granulation water). The mixture is stirred and mixed for 24 hours (the polymerization reaction takes place during the mixing process), granulated, washed and filtered with an ethanol / water mixture solution with a volume ratio of 8:2, fully dried at 160℃, and sieved through a 1.2 mm sieve to obtain high-performance conductive carbon black.
[0057] The oxidized conductive carbon black and acyl oxidized conductive carbon black products obtained in step S1 of this embodiment were characterized, and the results are as follows:
[0058] The oxygen-containing functional group content in the oxidized conductive carbon black obtained in step S1 is 2.5%;
[0059] The acyl group in the acyl-oxidized conductive carbon black obtained in step S2 is oleic acid acyl group, with a content of 2.3%.
[0060] Example 2
[0061] A method for preparing high-performance conductive carbon black, wherein the only difference from Example 1 is:
[0062] In step S1, the mass ratio of potassium permanganate to conductive carbon black raw material is 8:100 (the mass parts of conductive carbon black raw material are 100 parts).
[0063] Example 3
[0064] A method for preparing high-performance conductive carbon black, wherein the only difference from Example 1 is:
[0065] In step S1, the mass ratio of potassium permanganate to conductive carbon black raw material is 15:100 (the mass parts of conductive carbon black raw material are 100 parts).
[0066] Example 4
[0067] A method for preparing high-performance conductive carbon black, wherein the only difference from Example 1 is:
[0068] In step S1, the mass ratio of potassium permanganate to conductive carbon black raw material is 5:100 (the mass parts of conductive carbon black raw material are 100 parts).
[0069] Example 5
[0070] A method for preparing high-performance conductive carbon black, wherein the only difference from Example 1 is:
[0071] In step S2, oleic acid is added according to the mass-volume ratio of conductive carbon black raw material to oleic acid of 1g:10mL (the mass of conductive carbon black raw material remains unchanged).
[0072] Example 6
[0073] A method for preparing high-performance conductive carbon black, wherein the only difference from Example 1 is:
[0074] In step S2, oleic acid is added according to the mass-volume ratio of conductive carbon black raw material to oleic acid of 1g:15mL (the mass of conductive carbon black raw material remains unchanged).
[0075] Example 7
[0076] A method for preparing high-performance conductive carbon black, wherein the only difference from Example 1 is:
[0077] In step S2, oleic acid is added according to the mass-volume ratio of conductive carbon black raw material to oleic acid of 1g:0.5mL (the mass of conductive carbon black raw material remains unchanged).
[0078] Example 8
[0079] A method for preparing high-performance conductive carbon black, wherein the only difference from Example 1 is:
[0080] In step S2, for every 100 parts of acyl oxidized conductive carbon black, the amount of conductive polymer monomer added is 30 parts.
[0081] Example 9
[0082] A method for preparing high-performance conductive carbon black, wherein the only difference from Example 1 is:
[0083] In step S2, for every 100 parts of acyl oxidized conductive carbon black, the amount of conductive polymer monomer added is 45 parts.
[0084] Example 10
[0085] A method for preparing high-performance conductive carbon black, wherein the only difference from Example 1 is:
[0086] In step S2, for every 100 parts of acyl oxidized conductive carbon black, the amount of conductive polymer monomer added is 5 parts.
[0087] Example 11
[0088] A method for preparing high-performance conductive carbon black, wherein the only difference from Example 1 is:
[0089] In step S1, potassium permanganate is replaced with an equal mass of hydrogen peroxide.
[0090] Example 12
[0091] A method for preparing high-performance conductive carbon black, wherein the only difference from Example 1 is:
[0092] In step S2, oleic acid is replaced with an equal volume of palmitic acid.
[0093] Example 13
[0094] A method for preparing high-performance conductive carbon black, wherein the only difference from Example 1 is:
[0095] In step S2, pyrrole is replaced with an equal mass of aniline.
[0096] Comparative Example 1
[0097] A method for preparing modified conductive carbon black, wherein the only difference from Example 1 is:
[0098] Step S1 is skipped; the conductive carbon black raw material and the other preparation raw materials in S2 are directly fed into the stirring tooth granulator, and the remaining steps are the same as in Example 1.
[0099] Comparative Example 2
[0100] A method for preparing modified conductive carbon black, wherein the only difference from Example 1 is:
[0101] Step S2 is not performed.
[0102] Comparative Example 3
[0103] A method for preparing modified conductive carbon black, wherein the only difference from Example 1 is:
[0104] In step S2, oleic acid is replaced with an equal volume of oleyl alcohol.
[0105] Comparative Example 4
[0106] A method for preparing modified conductive carbon black, wherein the only difference from Example 1 is:
[0107] The step of treating the conductive carbon black raw material with an oxidant is omitted in step S1. After the oleic acid and the conductive carbon black raw material are mixed and reacted, an oleyl alcohol of the same volume as the oleic acid is added to carry out an acyl oxidation reaction.
[0108] The method for preparing conductive carbon black in this comparative example differs from that in Example 1 only in that:
[0109] S1. Conductive carbon black raw material is added to n-hexane at a ratio of 1g:100mL. Oleic acid and tetrabutylammonium bromide are added at a mass ratio of 100 parts conductive carbon black, 10 parts oleic acid and 1 part catalyst. After stirring and mixing for 24h, acidified conductive carbon black is obtained. Oleic alcohol is added to the reaction system at a mass-volume ratio of 1g:5mL for conductive carbon black raw material. After stirring and reacting for 24h, the mixture is washed and dried to obtain acyl-oxidized conductive carbon black.
[0110] The steps in step S2 are the same as in Example 1.
[0111] Comparative Example 5
[0112] A method for preparing modified conductive carbon black includes the following steps:
[0113] S1. The conductive carbon black raw material is fed into a stirring tooth granulator. The pyrrole monomer, ferric chloride and granulation water are mixed separately, fully atomized and injected into the granulator through a nozzle. The amount of each raw material added is as follows: 100 parts of conductive carbon black raw material, 15 parts of conductive polymer monomer, 13.5 parts of initiator, and 1.2 parts of sodium lignosulfonate (the sodium lignosulfonate is dissolved in 10 parts of water to obtain granulation water and then added in the form of granulation water). The mixture is stirred for 24 hours, granulated, washed and filtered with an ethanol / water mixture solution with a volume ratio of 8:2, dried thoroughly at 160℃, and sieved through a 1.2 mm sieve to obtain conductive carbon black with a conductive layer. The conductive carbon black with a conductive layer is added to n-hexane at a ratio of 1 g: 100 mL. Potassium permanganate and tetrabutylammonium bromide are added at a mass ratio of 100 parts of conductive carbon black with a conductive layer, 10 parts of oxidant and 1 part of catalyst. The mixture is stirred for 24 hours to obtain oxidized conductive carbon black.
[0114] S2. Oleic acid was added at a mass-to-volume ratio of 1g:5mL for oxidized conductive carbon black and oleic acid. After stirring and reacting for 24 hours, the mixture was washed and dried to obtain modified conductive carbon black.
[0115] Performance testing
[0116] Particle size test: The average particle size and particle size distribution index of the conductive carbon black prepared in each example and comparative example were measured on a nanoparticle size potentiometer using dynamic light scattering method. 10-15 conductive carbon black particles in the TEM image were observed to determine the particle size of the conductive carbon black and the average value was calculated.
[0117] Conductivity test: The intrinsic powder resistivity of the conductive carbon black prepared in each example and comparative example was tested using a four-probe tester. The lower the resistivity, the better the conductivity.
[0118] The performance test data is shown in Table 1 below:
[0119] Table 1. Performance test data of conductive carbon black obtained in the examples and comparative examples
[0120]
[0121]
[0122] As can be seen from Table 1 above, the high-performance conductive carbon black prepared by the present invention has the advantages of uniform particle size distribution and excellent conductivity. Its resistivity is as low as 3.36 Ω·cm and its particle size distribution index is as low as 0.51, indicating that the particle size distribution is uniform.
[0123] As can be seen from the data in Examples 1-4, the amount of oxidant added affects the content of oxygen-containing functional groups on the surface of conductive carbon black, which in turn affects the content of acyl groups in the subsequent acyl-oxidized conductive carbon black. This not only affects the electrostatic repulsion between carbon blacks, but also affects the subsequent grafting of conductive polymers. Therefore, when the mass ratio of oxidant to conductive carbon black raw material in step S1 is the preferred ratio of (8-10):100 of the present invention (Examples 1-2), the resulting high-performance conductive carbon black product has a lower particle size distribution index and resistivity, better conductivity, and more uniform particle size distribution.
[0124] According to Examples 1, 5-7, when the mass-to-volume ratio of conductive carbon black raw material to organic acid in step S1 is the preferred ratio of 1g:(1-10)mL (Examples 1 and 5), the content of acyl groups grafted onto the surface of the conductive carbon black is better, and the resulting carbon black product can also obtain a lower particle size distribution index. However, in Example 5, compared with Example 1, the amount of organic acid added is increased, and the content of acyl groups grafted onto the surface of the conductive carbon black is increased, which leads to an increase in steric hindrance for the formation of chemical bonds between the conductive polymer monomer and the carbon black during subsequent conductive coating, thus slightly reducing conductivity. In Example 6, the amount of organic acid added is further increased compared with Example 5, and the improvement in particle size distribution uniformity is generally moderate, but the conductivity of the carbon black is further reduced. In Example 7, the amount of organic acid added is too low. Although a small amount of acyl groups can still achieve sufficient electrostatic repulsion and obtain relatively good particle size distribution uniformity, it is not enough to generate enough hydroxyl groups to provide anchoring points for the conductive polymer layer when it is introduced in step S2, so the conductivity decreases significantly.
[0125] According to Examples 1, 8-10, when the mass fractions of each raw material in step S2 are 100 parts of acyl oxidized conductive carbon black, 10-30 parts of conductive polymer monomer, 6-30 parts of initiator, and 1.0-2.5 parts of binder (Examples 1, 8), a conductive layer with a more suitable thickness can be obtained, thus maximizing the improvement in conductivity of the conductive carbon black product.
[0126] According to Comparative Examples 1 and 2, omitting any step in this invention will result in the inability to obtain conductive carbon black that balances excellent conductivity and uniform particle size distribution.
[0127] According to Comparative Examples 3-4, the orientation of the ester bond is not suitable. Since the overall electronic effect of -COOR is electron-withdrawing, its introduction will reduce the electron cloud density on the carbon black surface. This results in a large tendency for electrostatic adsorption and aggregation between carbon black particles, which cannot improve the particle size uniformity of carbon black.
[0128] According to Comparative Example 5, coating with a conductive layer first and then performing acyl oxidation, although the introduction of acyl groups can still improve the uniformity of particle size distribution, the conductive layer cannot fully play its role, and the conductivity of carbon black decreases.
[0129] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. A method for preparing high-performance conductive carbon black, characterized in that, Includes the following steps: S1. Conductive carbon black raw material is treated sequentially with an oxidant and an organic acid to obtain acyl-oxidized conductive carbon black; S2. The acyl oxidized conductive carbon black obtained in step S1 is mixed with conductive polymer monomers, initiators and binders, and subjected to polymerization reaction and granulation to obtain high-performance conductive carbon black.
2. The method for preparing high-performance conductive carbon black as described in claim 1, characterized in that, Includes at least one of the following (a) to (c): (a) The mass ratio of the oxidant to the conductive carbon black raw material in step S1 is (8-10):100; (b) The mass-to-volume ratio of the conductive carbon black raw material to the organic acid in step S1 is 1g:(1-10)mL; (c) The mass fractions of each raw material in step S2 are: 100 parts of acyl oxidized conductive carbon black, 10-30 parts of conductive polymer monomer, 6-30 parts of initiator, and 1.0-2.5 parts of binder.
3. The method for preparing high-performance conductive carbon black as described in claim 1 or 2, characterized in that, Includes at least one of the following (d) to (h): (d) The oxidant in step S1 includes at least one of potassium permanganate, hydrogen peroxide, and ammonium persulfate; (e) The organic acid in step S1 includes at least one of oleic acid, palmitic acid, and acrylic acid; (f) The conductive polymer monomer in step S2 includes at least one of pyrrole, aniline, and thiophene; (g) The initiator in step S2 includes at least one of ferric chloride, potassium dichromate, potassium iodate, manganese dioxide, and benzoyl peroxide; (h) The binder in step S2 includes lignin sulfonate.
4. The method for preparing high-performance conductive carbon black as described in claim 1, characterized in that, The mass percentage of acyl groups in the acyl-oxidized conductive carbon black obtained in step S1 is 1.8–3.5%.
5. The method for preparing high-performance conductive carbon black as described in claim 1, characterized in that, Includes at least one of the following (i) to (k): (i) Step S1 involves treating the conductive carbon black raw material with an oxidant in a solution environment, wherein the solution includes an organic solvent, and the organic solvent includes at least one of dichloromethane, dimethyl sulfoxide, and n-hexane; (j) Step S1 involves treating the conductive carbon black raw material with an oxidant in the presence of a catalyst, wherein the catalyst includes tetrabutylammonium bromide; (k) Step S2 includes a sieving step after granulation, wherein the sieve used for sieving has a mesh size of 1 to 2 mm.
6. The method for preparing high-performance conductive carbon black as described in claim 1, characterized in that, The conductive carbon black raw material mentioned in step S1 has an average particle size of 20-60 nm, an iodine absorption value of 50-100 g / kg, and an ash content of ≤0.1%.
7. High-performance conductive carbon black prepared by the preparation method according to any one of claims 1 to 6.
8. A high-voltage cable shielding layer, characterized in that, The raw materials for its preparation include the high-performance conductive carbon black described in claim 7.
9. The high-voltage cable shielding layer as described in claim 8, characterized in that, The following raw materials are included in the preparation, calculated by parts by mass: 27-35 parts of the high-performance conductive carbon black as described in claim 7, 60-70 parts of the matrix resin, 0.1-0.5 parts of antioxidant, and 2-4 parts of crosslinking agent.
10. A high-voltage cable, comprising the high-voltage cable shielding layer of claim 8 or 9.